ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒæ•™è‚²å¦é™¢æ±‰è¯ä¸“ä¸š2015å±Šå¦ç”Ÿ ä½¿ç”¨åè¯â€œåŽæ¥â€å’Œâ€œä»¥åŽâ€çš„åè¯¯åˆ†æž - Mayasari, A?an Rifanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract In Mandarin learning, grammar has a very important role. The noun is one of the most important parts of grammar, including the noun